Non-fluorine proton exchange membrane with controllable sulfonation sites as well as preparation method and application of non-fluorine proton exchange membrane

By accurately controlling the reaction steps of the sulfonation site, a regular sulfonate connection structure is formed, which solves the problem that the existing non-fluorine proton exchange membrane is difficult to control the sulfonation site during the preparation process, and achieves efficient proton conduction and mechanical stability sex.

CN119463079APending Publication Date: 2025-02-18FOSHAN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411669726.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing non-fluorine proton exchange membranes are difficult to control the sulfonation site during the preparation process, resulting in immature ion cluster structures, affecting their ion conductivity and chemical stability.

Method used

By synthesizing monomers with specific structures and using precisely controlled sulfonation reaction steps, a regular sulfonate connection structure is formed to improve the swelling and mechanical properties of the film.

Benefits of technology

The controllability of the sulfonation site is achieved, the proton conductivity, mechanical stability and oxidation resistance of the proton exchange membrane are improved, and it is suitable for fuel cells, electrolytic hydrogen production and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005145510120000021
    Figure BDA0005145510120000021
  • Figure BDA0005145510120000031
    Figure BDA0005145510120000031
  • Figure BDA0005145510120000032
    Figure BDA0005145510120000032
Patent Text Reader

Abstract

The invention belongs to the technical field of proton exchange membranes, particularly discloses a sulfonation-site-controllable non-fluorine proton exchange membrane as well as a preparation method and application thereof, and develops a sulfonation-site-controllable non-fluorine ionomer proton exchange membrane synthesis method, the main chain of the proton exchange membrane does not contain heteroatoms such as oxygen and sulfur, and the proton exchange membrane is high in hydrolysis resistance and acid resistance stability; due to an all-carbon-carbon connection structure, hydroxyl radicals are not easy to attack the polymer, so that the free radical resistance stability of the polymer is improved; meanwhile, as for ion exchange resin prepared through traditional polymerization-random sulfonation, sulfonate radicals of the polymer are connected to a long alkane side chain, arrangement is regular, swelling of the polymer is small, and size stability is good; proton exchange membranes of different IECs can be obtained by adjusting the proportion of optional formula 3A. The proton exchange membrane prepared by the invention has low water absorption rate, high proton conductivity, high mechanical stability and antioxidant stability, and can be used as electrolyte materials for fuel cells, water electrolysis hydrogen production, flow cells, electrodialysis and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of proton exchange membranes, in particular to a non-fluorine proton exchange membrane with controllable sulfonation sites and a preparation method and application thereof. Background Art

[0002] Proton exchange membrane (PEM) plays a vital role in electrochemical devices such as water electrolysis, fuel cells, flow batteries, and electrodialysis. It is mainly responsible for transmitting protons, blocking electrons and reaction gases. Its cost, performance, and durability directly determine the cost-effectiveness and life of electrochemical devices. The current mainstream perfluorosulfonic acid (such as the Nafion series) has a high cost and is one of the main components of the cost of the electrolyzer. The PFSA membrane has low tensile strength and is easily damaged at the edges or pierced by the diffusion layer fibers during assembly of the electrolyzer and fuel cell. Due to the special molecular structure of PFSA, its gas permeability is high, and it is prone to "gas cross-talk" and other situations. In addition, PFSA uses perfluorinated materials, and the degradation products are more polluting to the environment. Therefore, developed countries such as the European Union and the United States have introduced "fluorine restrictions".

[0003] In view of the above-mentioned shortcomings of PFSA membrane materials, the industry has developed hydrocarbon-based proton exchange membranes, such as Chinese patent application number CN01132100.8 discloses a polytrifluorostyrene fluorine-containing exchange resin in polytrifluorostyrene CN1128679C, which is obtained by sulfonating the benzene ring of the polytrifluorostyrene side chain to obtain a polytrifluorostyrene proton exchange membrane. However, due to the styrene structure, the resin is brittle, the low molecular weight leads to high membrane swelling, and the mechanical strength is low, which makes it difficult to meet the harsh working conditions such as water electrolysis and fuel cells.

[0004] Chinese patent application number CN201910686281.3 discloses a densely sulfonated fluorinated polyarylether compound, which directly sulfonates the benzene ring in the polymer to prepare a non-fluorinated sulfonic acid resin. However, due to the violent reaction between the benzene ring and the sulfonation reagent, it is difficult to control the sulfonation site, and the ion cluster structure cannot be formed, and its ion conductivity is poor. In addition, the contained heteroatom structure is easily attacked by free radicals in an acidic working environment, and the chemical stability is poor.

[0005] At present, most non-fluorinated ionomer proton exchange membranes are prepared by a synthesis route of first synthesis and then random sulfonation. Since the sulfonation reaction is difficult to accurately control, the sites where the sulfonate groups are generated are disordered, making it difficult to form an effective polar-nonpolar chemical structure. As a result, the prepared membranes have large swelling, poor mechanical properties and chemical stability. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a non-fluorine proton exchange membrane with controllable sulfonation sites, and a preparation method and application thereof.

[0007] To achieve the above object, the present invention is implemented according to the following technical solutions:

[0008] One of the technical solutions of the present invention is a method for preparing a non-fluorinated proton exchange membrane with controllable sulfonation sites, comprising the following steps:

[0009] S1. A mixture of a structural monomer of Formula 1A and a structural monomer of Formula 3A, with a molar ratio of 1 to 1.5, and a structural monomer of Formula 2A are dissolved in 60 mL of dichloromethane DCM, cooled to 0°C with an ice bath, 79.6 mL of trifluoromethanesulfonic acid is added dropwise, and polymerized for 2 h to 12 d under ice bath conditions after the addition is complete; after the reaction is complete, dimethyl sulfoxide DMSO is added to quench and dissolve the polymer, and the solid is sunk into ice water to obtain a white solid, which is repeatedly rinsed with deionized water several times and then vacuum dried at 80°C for 12 to 48 h to obtain a first intermediate polymer; wherein the structural formulas of Formula 1A, Formula 2A and Formula 3A are respectively:

[0010]

[0011]

[0012] In Formula 1A: q represents an integer between 0 and 10; R0 is an alkylene group or oxygen or sulfur or nitrogen or a substituent having the following structure:

[0013]

[0014] R 150 , R 160 , R 170 , R 180 Each is independently one of sulfonic acid, hydrogen, halide, alkyl, alkenyl, alkynyl and aryl, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with halide;

[0015] As an example, one of the monomers of formula 1A is 5-bromotrifluoropentanone; as another example, one of the monomers of formula 1A is 7-bromotrifluoroheptanone; in other cases, the trifluoromonomer q of formula 1A is selected from an integer between 0 and 10;

[0016] In Formula 2A: n represents an integer between 0 and 5; R 10 , R 20 , R 30 , R 40 , R 50 , R 60 , R 70 and R 80 are each independently one of sulfonic acid, hydrogen, halide, alkyl, alkenyl, alkynyl and aryl, wherein the alkyl, alkenyl, alkynyl or aryl is optionally substituted with halide, and wherein R 30 and R60 Optionally connected to a halide or alkyl substituted five-membered ring; the structural unit monomer of formula 2A has the following structure but is not limited to:

[0017]

[0018] As an example, one of the monomers of Formula 2A is biphenyl; as another example, one of the monomers of Formula 2A is p-terphenyl; as yet another example, one of the monomers of Formula 2A is m-terphenyl; in other cases, an aromatic monomer having Formula 2A;

[0019] In Formula 3A: R 100 is independently a nitrogen-containing heterocycle or an alkyl or alkenyl or alkynyl group or a substituent having formula 1B:

[0020]

[0021] The nitrogen-containing heterocyclic group is one of substituted pyrrole, pyrroline, pyrazole, pyrazoline, imidazole, imidazoline, triazole, pyridine, triazine, pyrazine, pyridazine, pyrimidine, azepine, quinoline, piperidine, pyrrolidine, pyrazolidine, imidazolidine, azepane, isoxazole, isoxazoline, oxazole, oxazoline, oxadiazole, oxatriazole, dioxazole, oxazine, oxadiazine, isoxazolidine, morpholine, thiazole, isothiazole, oxathiazole, oxathiazine and caprolactam, wherein each substituent is independently one of sulfonic acid group, alkyl, alkenyl, alkynyl, aryl and aralkyl, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with a halide;

[0022] R 90 , R 110 , R 120 , R 130 and R140 Each is independently one of sulfonic acid, hydrogen, halide, alkyl, alkenyl, alkynyl and aryl, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with halide;

[0023] Representative monomers of formula 3A include but are not limited to: As an example, one of the monomers of formula 3A is trifluorobutanone; as another example, one of the monomers of formula 2A is trifluoroacetophenone; as yet another example, one of the monomers of formula 2A is 1-(3,5-bis(trifluoromethyl)phenyl)-2,2,2-trifluoroethanone; in other cases, a trifluoro monomer having the above formula 3A;

[0024] S2, taking the first intermediate polymer and potassium thioacetate KSAc in a molar ratio of 1 to 1.5, adding them to a single-necked round-bottom flask containing 200 mL of dimethylacetamide DMAc, then heating the solution to 30 to 100° C. in an oil bath, and reacting for 1 h to 24 hours; after cooling to room temperature, precipitating the solution into 1000 mL of methanol, and stirring for 0.5 hours; filtering the obtained polymer by vacuum filtration, dissolving it in 100 mL of tetrahydrofuran THF, and precipitating the polymer solution into 500 mL of methanol again, vacuum filtration, and drying the polymer at 80° C. in vacuum for 12 to 48 hours to obtain a second intermediate polymer;

[0025] S3. Take the second intermediate polymer and mCPBA with a molar ratio of 1 to 5, dissolve the second intermediate polymer in 18 mL of dimethylacetamide DMAc in a 100 mL single-necked round-bottom flask, cool the flask to 0°C in an ice bath, add mCPBA after 10 minutes, heat the flask to room temperature after the mCPBA is completely added, stir for 1 hour, and then precipitate into 50 mL of 1 M sodium chloride solution, stirring for 0.5 h; the obtained polymer is vacuum filtered, dissolved in 10 mL of dimethyl sulfoxide DMSO, and then precipitated into 50 mL of acetone, stirring for 0.5 h; similarly, the precipitated polymer is filtered, and then dried in a vacuum at 40 to 150°C for 12 to 48 h to obtain an ionic polymer in the form of sodium ions;

[0026] S4. Dissolve the ionic polymer in a polar solvent to obtain a solution with a concentration of 5wt% to 40wt%, centrifuge, cast it on a substrate or a porous substrate, and then vacuum dry it at 80°C for 12 hours to obtain a sodium ion exchange membrane with a thickness of 10 to 100μm; place the sodium ion exchange membrane in 1M sulfuric acid for 24 hours, then rinse it with deionized water to neutrality, and then place these membranes in deionized water for 24 hours, change the deionized water three times within 24 hours to obtain a proton exchange membrane.

[0027] The structural formula of the representative proton exchange membrane synthesized by the present invention is as follows:

[0028]

[0029]

[0030]

[0031] In the structural formula of the above representative proton exchange membrane, x represents the molar ratio of the monomer of the structural formula 1A to the monomer of the structural formula 2A, which is 1 to 100; and m represents the degree of polymerization, which is an integer between 10 and 1000.

[0032] Preferably, the porous substrate has a thickness of 1 to 100 μm.

[0033] Preferably, the polar solvent is one or more of NMP, DMF, DMSO and DMAc.

[0034] Preferably, the substrate is one of a stainless steel plate, a glass plate, a polyethylene terephthalate plastic PET plate, a polypropylene PP plate, and a polyethylene naphthalate PEN plate; the porous substrate is one of a polyphenylene sulfide PPS orifice plate, a polyether ketone resin PEK orifice plate, a polyethylene terephthalate plastic PET orifice plate, a polytetrafluoroethylene orifice plate, a stainless steel plate orifice plate, a polypropylene PP orifice plate, a polyethylene PE orifice plate, and a glass fiber cloth.

[0035] The second technical solution of the present invention is a non-fluorine proton exchange membrane with controllable sulfonation sites prepared by the above method.

[0036] The third technical solution of the present invention is the use of a non-fluorinated proton exchange membrane with controllable sulfonation sites in the preparation of electrolyte materials for fuel cells and / or water electrolysis to produce hydrogen and / or flow batteries and / or electrodialysis.

[0037] Compared with the prior art, the present invention synthesizes a non-fluorinated ionomer proton exchange membrane with controllable sulfonation sites. The main chain of the proton exchange membrane does not contain heteroatoms such as oxygen and sulfur, is resistant to hydrolysis, and has strong acid resistance stability; its all-carbon-carbon connected structure makes it difficult for hydroxyl radicals to attack the polymer, thereby improving its free radical resistance stability; at the same time, for the traditional ion exchange resin prepared by first polymerization-then random sulfonation, the polymer sulfonate group is connected to the long alkane side chain, the arrangement is regular, the polymer swelling is small, and the dimensional stability is good; the proton exchange membrane with different IEC can be obtained by adjusting the ratio of the optional formula 3A. The proton exchange membrane prepared by the present invention has low water absorption, high proton conductivity, high mechanical stability, and anti-oxidation stability, and can be used as an electrolyte material for fuel cells, water electrolysis hydrogen production, liquid flow batteries, electrodialysis, purification, etc. DETAILED DESCRIPTION

[0038] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with embodiments. The specific embodiments described herein are only used to explain the present invention and are not used to limit the invention.

[0039] In the following examples, representative monomers of Formula 1A, Formula 2A and Formula 3A were used to prepare non-fluorinated proton exchange membranes with controllable sulfonation sites. The raw materials and reagents used were commercially available or prepared by conventional methods in the art unless otherwise specified.

[0040] Example 1

[0041] Proton exchange membranes were prepared from trifluorobutanone, 5-bromo-1,1,1-trifluoropentane-2-one and p-terphenyl (named sPTP-1-x, where x is the molar ratio of 5-bromo-1,1,1-trifluoropentane-2-one to p-terphenyl, which is 1 to 100). Proton exchange membrane sample 1sPTP-1-x was prepared by the following three main steps: (1) synthesis of polymer backbone, (2) sulfonation of polymer, and (3) membrane forging and proton exchange.

[0042] The structural formula of proton exchange membrane sample 1 is as follows:

[0043]

[0044] (1) Synthesis of polymer backbone (PTP-1-10): Dissolve trifluorobutanone (1.26 g, 0.01 mol), p-terphenyl (23 g, 0.1 mol), and 5-bromotrifluoropentanone (19.62 g, 0.09 mol) in 60 mL DCM, cool to 0°C with an ice bath, and drop TFSA (79.6 mL, 0.9 mol). After the addition is complete, polymerize under ice bath conditions for 2 h-12 d. After the reaction is complete, add DMSO to quench and dissolve the polymer, sink it into ice water to obtain a white solid, rinse it repeatedly with deionized water several times, and then dry it in a vacuum at 80°C for 12 h to obtain the first intermediate polymer;

[0045] (2) Sulfonation of polymer (sPTP-1-10): In a 500 mL single-necked round-bottom flask, the first intermediate polymer (10.94 g, 26 mmol), KSAc (3.28 g, 28.7 mmol) and DMAc (200 mL) were added and heated to 50 °C and stirred for 4 h. The solution became turbid due to the insoluble potassium bromide formed during the reaction. The solution was then cooled to room temperature, the ice bath was cooled to 0 °C, and mCPBA (21.2 g, 86.1 mmol) was added proportionally after 1 hour. After the complete addition of mCPBA, the solution was removed from the ice bath and stirred at room temperature for 1 hour. The solution was poured into 800 mL of 1 M sodium chloride and stirred for 1 h. The polymer was filtered, rinsed with deionized water, and dissolved in 100 mL of DMSO. The solution was then precipitated into 500 mL of acetone. The final polymer was filtered and dried under vacuum at 80 °C for more than 12 h. Other sPTP-1-x membranes were prepared by using different molar ratios of 5-bromo-1,1,1-trifluoropentan-2-one to p-terphenyl.

[0046] (3) Forging membrane and proton exchange: The obtained polymer is dissolved in a polar solvent (NMP, DMF, DMSO, DMAc, etc.), centrifuged, cast on a glass plate or a stainless steel plate, dried at 60-100°C for 5-24 hours to form a membrane, and then vacuum dried at 80-150°C for 5-24 hours. The membrane thickness is between 10 and 100 μm. The membrane is immersed in a 1M sulfuric acid solution at 80°C for 24 hours to obtain a proton exchange membrane sample 1.

[0047] Example 2

[0048] Polyelectrolytes were prepared from trifluoroacetophenone, 5-bromo-1,1,1-trifluoropentane-2-one and p-terphenyl (named sPTP-2-x, where x is the molar ratio of 5-bromo-1,1,1-trifluoropentane-2-one to p-terphenyl, ranging from 1 to 100). Proton exchange membrane sample 2sPTP-2-x was prepared by the following three main steps: (1) synthesis of polymer backbone, (2) sulfonation of polymer, and (3) membrane forging and proton exchange.

[0049] The structural formula of proton exchange membrane sample 2 is as follows:

[0050]

[0051] (1) Synthesis of polymer backbone (PTP-2-10): Dissolve trifluoroacetophenone (1.74 g, 0.01 mol), p-terphenyl (23 g, 0.1 mol), and 5-bromotrifluoropentanone (19.62 g, 0.09 mol) in 60 mL DCM, cool to 0°C with an ice bath, and dropwise add TFSA (79.6 mL, 0.9 mol). After the addition is complete, polymerize in an ice bath for 2 h to 12 d. After the reaction is complete, add DMSO to quench and dissolve the polymer, sink it in ice water to obtain a white solid, rinse it several times with deionized water, and then vacuum dry it at 80°C for 12 h to obtain the first intermediate polymer.

[0052] (2) Sulfonation of polymer (sPTP-2-10): In a 500 mL single-necked round-bottom flask, the first intermediate polymer (11.06 g, 26 mmol), KSAc (3.28 g, 28.7 mmol) and DMAc (200 mL) were added and heated to 50 °C and stirred for 4 h. The solution became turbid due to the insoluble potassium bromide formed during the reaction. The solution was then cooled to room temperature, the ice bath was cooled to 0 °C, and mCPBA (21.2 g, 86.1 mmol) was added proportionally after 1 hour. After the mCPBA was completely added, the solution was removed from the ice bath and stirred at room temperature for 1 hour. The solution was poured into 800 mL of 1 M sodium chloride and stirred for 1 h. The polymer was filtered, rinsed with deionized water, and dissolved in 100 mL of DMSO. The solution was then precipitated into 500 mL of acetone. The final polymer was filtered and dried under vacuum at 80 °C for more than 12 h. Other sPTP-2-x membranes were prepared by using different molar ratios of 5-bromo-1,1,1-trifluoropentan-2-one to trifluorobutanone.

[0053] (3) Forging membrane and proton exchange: The obtained polymer was dissolved in a polar solvent (NMP, DMF, DMSO, DMAc, etc.), centrifuged, cast on a glass plate or a stainless steel plate, dried at 60-100°C for 5-24 hours to form a membrane, and then vacuum dried at 80-150°C for 5-24 hours. The membrane thickness was between 10 and 100 μm. The membrane was immersed in a 1M sulfuric acid solution at 80°C for 24 hours to obtain a proton exchange membrane sample 2.

[0054] Example 3

[0055] Polyelectrolytes were prepared from trifluorobutanone, 5-bromo-1,1,1-trifluoropentane-2-one and biphenyl (named sBPTP-3-x, where x is the molar ratio of 5-bromo-1,1,1-trifluoropentane-2-one to biphenyl, ranging from 1 to 100). Proton exchange membrane sample 3sBPTP-3-x was prepared by the following three main steps: (1) synthesis of polymer backbone, (2) sulfonation of polymer, and (3) membrane forging and proton exchange.

[0056] The structural formula of proton exchange membrane sample 3 is as follows:

[0057]

[0058] (1) Synthesis of polymer backbone (sBPTP-3-70): Dissolve trifluorobutanone (3.78 g, 0.03 mol), biphenyl (15.6 g, 0.1 mol), and 5-bromotrifluoropentanone (15.26 g, 0.07 mol) in 60 mL DCM, cool to 0°C with an ice bath, and drop TFSA (79.6 mL, 0.9 mol). After the addition is complete, polymerize in an ice bath for 2 h-12 d. After the reaction is complete, add DMSO to quench and dissolve the polymer, sink it in ice water to obtain a white solid, rinse it repeatedly with deionized water several times, and then dry it in a vacuum at 80°C for 12 h to obtain the first intermediate polymer;

[0059] (2) Sulfonation of polymer (sBPTP-3-70): In a 500 mL single-necked round-bottom flask, the first intermediate polymer (8.56 g, 26 mmol), KSAc (3.28 g, 28.7 mmol) and DMAc (200 mL) were added and heated to 50 °C and stirred for 4 h. The solution became turbid due to the insoluble potassium bromide formed during the reaction. The solution was then cooled to room temperature, the ice bath was cooled to 0 °C, and mCPBA (21.2 g, 86.1 mmol) was added proportionally after 1 hour. After the complete addition of mCPBA, the solution was removed from the ice bath and stirred at room temperature for 1 hour. The solution was poured into 800 mL of 1 M sodium chloride and stirred for 1 h. The polymer was filtered, rinsed with deionized water, and dissolved in 100 mL of DMSO. The solution was then precipitated into 500 mL of acetone. The final polymer was filtered and dried under vacuum at 80 °C for more than 12 h. Other sBPTP-3-x membranes were prepared by using different molar ratios of 5-bromo-1,1,1-trifluoropentan-2-one to biphenyl.

[0060] (3) Forging membrane and proton exchange: The obtained polymer was dissolved in a polar solvent (NMP, DMF, DMSO, DMAc, etc.), centrifuged, cast on a glass plate or a stainless steel plate, dried at 60-100°C for 5-24 hours to form a membrane, and then vacuum dried at 80-150°C for 5-24 hours. The membrane thickness was between 10 and 100 μm. The membrane was immersed in a 1M sulfuric acid solution at 80°C for 24 hours to obtain a proton exchange membrane sample 3.

[0061] Example 4

[0062] The polyelectrolyte was prepared from trifluorobutanone, 5-bromo-1,1,1-trifluoropentane-2-one and m-terphenyl (named smPTP-4-x, where x is the molar ratio of 5-bromo-1,1,1-trifluoropentane-2-one to m-terphenyl, which is 1 to 100). The proton exchange membrane sample 4 smPTP-4-x was prepared by the following three main steps: (1) synthesis of the polymer backbone, (2) sulfonation of the polymer, and (3) membrane forging and proton exchange. The structural formula of the proton exchange membrane sample 4 is as follows:

[0063]

[0064] Example 5

[0065] The polyelectrolyte was prepared from trifluorobutanone, 7-bromo-1,1,1-trifluoroheptane-2-one and p-terphenyl (named sPTP-5-x, where x is the molar ratio of 5-bromo-1,1,1-trifluoropentane-2-one to straight terphenyl, which is 1 to 100). The proton exchange membrane sample 5 sPTP-5-x was prepared by the following three main steps: (1) synthesis of the polymer backbone, (2) sulfonation of the polymer, and (3) membrane forging and proton exchange. The structural formula of the proton exchange membrane sample 5 is as follows:

[0066]

[0067] Example 6

[0068] The polyelectrolyte was prepared from trifluorobutanone, 1-(4-(3-bromopropyl)phenyl)-2,2,2-trifluoroethanone and p-terphenyl (named sPTP-6-x, where x is the molar ratio of 1-(4-(3-bromopropyl)phenyl)-2,2,2-trifluoroethanone to p-terphenyl, which is 1 to 100). The proton exchange membrane sample 6sPTP-6-x was prepared by the following three main steps: (1) synthesis of the polymer backbone, (2) sulfonation of the polymer, and (3) membrane forging and proton exchange. The structural formula of the proton exchange membrane sample 6 is as follows:

[0069]

[0070] Example 7

[0071] The polyelectrolyte was prepared from trifluoroacetophenone, 1-(4-(3-bromopropyl)phenyl)-2,2,2-trifluoroethanone and p-terphenyl (named sPTP-7-x, where x is the molar ratio of 1-(4-(3-bromopropyl)phenyl)-2,2,2-trifluoroethanone to p-terphenyl, which is 1 to 100). The proton exchange membrane sample 7sPTP-7-x was prepared by the following three main steps: (1) synthesis of the polymer backbone, (2) sulfonation of the polymer, and (3) membrane forging and proton exchange. The structural formula of the proton exchange membrane sample 7 is as follows:

[0072]

[0073] Example 8

[0074] The polyelectrolyte was prepared from trifluoroacetophenone, 2,2,2-trifluoro-1-(perfluorophenyl)ethanone and p-terphenyl (named sPTP-8-x, where x is the molar ratio of 2,2,2-trifluoro-1-(4-iodophenyl)ethanone to p-terphenyl, which is 1 to 100). The proton exchange membrane sample 8sPTP-8-x was prepared by the following three main steps: (1) synthesis of the polymer backbone, (2) sulfonation of the polymer, and (3) membrane forging and proton exchange. The structural formula of the proton exchange membrane sample 8 is as follows:

[0075]

[0076] The difference from Example 1 is that the sulfonation step is replaced by NaSH and then oxidized with hydrogen peroxide to obtain the product.

[0077] Example 9

[0078] The polyelectrolyte was prepared from trifluorobutanone, 2,2,2-trifluoro-1-(perfluorophenyl)ethanone and p-terphenyl (named sPTP-8-x, where x is the molar ratio of 2,2,2-trifluoro-1-(4-iodophenyl)ethanone to p-terphenyl, which is 1 to 100). The proton exchange membrane sample 9 sPTP-9-x was prepared by the following three main steps: (1) synthesis of the polymer backbone, (2) sulfonation of the polymer, and (3) membrane forging and proton exchange. The structural formula of the proton exchange membrane sample 9 is as follows:

[0079]

[0080] The difference from Example 1 is that the sulfonation step is replaced by NaSH and then oxidized with hydrogen peroxide to obtain the product.

[0081] Example 10

[0082] The polyelectrolyte was prepared from 5-bromo-1,1,1-trifluoropentane-2-one, 1-(4-(3-bromopropyl)phenyl)-2,2,2-trifluoroethanone and p-terphenyl (named sPTP-10-x, where x is the molar ratio of 1-(4-(3-bromopropyl)phenyl)-2,2,2-trifluoroethanone to p-terphenyl, which is 1 to 100). The proton exchange membrane sample 10sPTP-10-x was prepared by the following three main steps: (1) synthesis of the polymer backbone, (2) sulfonation of the polymer, and (3) membrane forging and proton exchange. The structural formula of the proton exchange membrane sample 10 is as follows:

[0083]

[0084] Embodiment 11

[0085] The polyelectrolyte was prepared from 1-(3,5-bis(trifluoromethyl)phenyl)-2,2,2-trifluoroethanone, 5-bromo-1,1,1-trifluoropentane-2-one and p-terphenyl (named sPTP-11-x, where x is the molar ratio of 5-bromo-1,1,1-trifluoropentane-2-one to p-terphenyl, which is 1 to 100). The proton exchange membrane sample 11sPTP-11-x was prepared by the following three main steps: (1) synthesis of the polymer backbone, (2) sulfonation of the polymer, and (3) membrane forging and proton exchange. The structural formula of the proton exchange membrane sample 11 is as follows:

[0086]

[0087] The following performance tests were performed on the proton exchange membrane samples prepared in Examples 1 to 3 respectively:

[0088] The ion exchange capacity (IEC), water absorption and conductivity of the proton exchange membrane samples were determined according to the method for determining the ion exchange capacity of proton exchange membrane GB / T 20042.3-2022: the pre-dried membrane was weighed (W membrane), soaked in 25 mL of 2M NaCl solution for 24 h, then the membrane was taken out of the solution and titrated to neutral pH with 0.01M NaOH standard solution, using phenolic acid as an indicator. The consumption of NaOH was recorded as VNaOH. The titration was averaged three times, and the IEC results were calculated using formula (1) as shown in Table 1.

[0089] IEC=0.01*V NaOH / W 膜 (1).

[0090] Table 1

[0091]

[0092] Fenton's reagent test:

[0093] The Fenton reagent (3% hydrogen peroxide solution, 2 ppm Fe 2+ )The oxidative stability of the proton exchange membrane samples was tested. 50 mg of dry proton exchange membrane sample was immersed in Fenton's reagent at a concentration of 80°C. After 1 hour, the membrane was removed from Fenton's reagent, washed with distilled water, and balanced in distilled water for at least 24 hours. The proton exchange membrane sample was dried and weighed. The residual mass was calculated based on the mass of the membrane after immersion in the Fenton test at 80°C for 1 hour. The conductivity changes of the membrane under the conditions of 25°C and 100% RH before and after immersion are measured as shown in Table 2.

[0094] Table 2

[0095]

[0096] Electrolyzer unit testing: Although proton exchange membrane samples are expected to have excellent chemical stability, hydroxide conductivity, low water absorption, good solubility and mechanical properties, the most practical evaluation of these materials is their performance in an electrolyzer. The membrane electrode assembly (MEA) is prepared by spraying the electrode catalyst and ionomer on both sides of the proton exchange membrane sample using a robotic sprayer. Slurry preparation: The membrane electrode assembly (MEA) is obtained by dissolving the catalyst (Pt / C, IrO2) and a certain amount of proton exchange membrane sample in DMF, ultrasonically treating it for 1 hour, and then using a spraying equipment to spray the prepared slurry on both sides of the proton exchange membrane sample, and drying it. Performance test: Proton exchange membrane sample, ionomer loading is 20%, catalyst: 1 mgPt / C / cm on the anode 2 , 0.5mg IrO2 / cm on cathode 2 Test conditions: 80°C water and electrolytic cell, water flow rate: 3.0 ml / min). Usually, the battery cell is at 100 mA / cm 2 30 min at 200 mA / cm 2 After activation, the current density change at 2V constant voltage was recorded.

[0097] Test results: When the voltage is 2V, the current density of PEM sample 1-PEM sample 3 is at least 3A / cm 2 .

[0098] The mechanical properties of proton exchange membrane sample 1 were determined according to the mechanical property test method of proton exchange membrane GB / T 20042.3-2022: a proton exchange membrane sample of 80 μm was forged, and its mechanical properties were tested. The test data are shown in Table 3.

[0099] Table 3

[0100]

[0101] In summary, the proton prepared by the present invention has high proton conductivity and high mechanical stability and anti-oxidation stability, and can be used as electrolyte materials for fuel cells, water electrolysis to produce hydrogen, liquid flow batteries, electrodialysis, etc.

[0102] The technical solution of the present invention is not limited to the above-mentioned specific embodiments. All technical variations made according to the technical solution of the present invention fall within the protection scope of the present invention.

Claims

1. A method for preparing a non-fluorinated proton exchange membrane with controllable sulfonation sites, characterized in that: The following steps are involved: S1. A mixture of a structural monomer of Formula 1A and a structural monomer of Formula 3A, with a molar ratio of 1 to 1.5, and a structural monomer of Formula 2A are dissolved in 60 mL of dichloromethane DCM, cooled to 0°C with an ice bath, 79.6 mL of trifluoromethanesulfonic acid is added dropwise, and polymerized for 2 h to 12 d under ice bath conditions after the addition is complete; after the reaction is complete, dimethyl sulfoxide DMSO is added to quench and dissolve the polymer, and the solid is sunk into ice water to obtain a white solid, which is repeatedly rinsed with deionized water several times and then vacuum dried at 80°C for 12 to 48 h to obtain a first intermediate polymer; wherein the structural formulas of Formula 1A, Formula 2A and Formula 3A are respectively: In Formula 1A: q represents an integer between 0 and 10; R0 is an alkylene group or oxygen or sulfur or nitrogen or a substituent having the following structure: R 150 , R 160 , R 170 , R 180 Each is independently one of sulfonic acid, hydrogen, halide, alkyl, alkenyl, alkynyl and aryl, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with halide; In Formula 2A: n represents an integer between 0 and 5; R 10 , R 20 , R 30 , R 40 , R 50 , R 60 , R 70 and R 80 are each independently one of sulfonic acid, hydrogen, halide, alkyl, alkenyl, alkynyl and aryl, wherein the alkyl, alkenyl, alkynyl or aryl is optionally substituted with halide, and wherein R 30 and R 60 an optionally attached halide or alkyl substituted five-membered ring; In Formula 3A: R 100 is independently a nitrogen-containing heterocycle or an alkyl or alkenyl or alkynyl group or a substituent having formula 1B: The nitrogen-containing heterocyclic group is one of substituted pyrrole, pyrroline, pyrazole, pyrazoline, imidazole, imidazoline, triazole, pyridine, triazine, pyrazine, pyridazine, pyrimidine, azepine, quinoline, piperidine, pyrrolidine, pyrazolidine, imidazolidine, azepane, isoxazole, isoxazoline, oxazole, oxazoline, oxadiazole, oxatriazole, dioxazole, oxazine, oxadiazine, isoxazolidine, morpholine, thiazole, isothiazole, oxathiazole, oxathiazine and caprolactam, wherein each substituent is independently one of sulfonic acid group, alkyl, alkenyl, alkynyl, aryl and aralkyl, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with a halide; R 90 , R 110 , R 120 , R 130 and R140 Each is independently one of sulfonic acid, hydrogen, halide, alkyl, alkenyl, alkynyl and aryl, and the alkyl, alkenyl, alkynyl or aryl is optionally substituted with halide; S2, taking the first intermediate polymer and potassium thioacetate KSAc in a molar ratio of 1 to 1.5, adding them to a single-necked round-bottom flask containing 200 mL of dimethylacetamide DMAc, then heating the solution to 30 to 100° C. in an oil bath, and reacting for 1 h to 24 hours; after cooling to room temperature, precipitating the solution into 1000 mL of methanol, and stirring for 0.5 hours; filtering the obtained polymer by vacuum filtration, dissolving it in 100 mL of tetrahydrofuran THF, and precipitating the polymer solution into 500 mL of methanol again, vacuum filtration, and drying the polymer at 80° C. in vacuum for 12 to 48 hours to obtain a second intermediate polymer; S3. Take the second intermediate polymer and mCPBA with a molar ratio of 1 to 5, dissolve the second intermediate polymer in 18 mL of dimethylacetamide DMAc in a 100 mL single-necked round-bottom flask, cool the flask to 0°C in an ice bath, add mCPBA after 10 minutes, heat the flask to room temperature after the mCPBA is completely added, stir for 1 hour, and then precipitate into 50 mL of 1 M sodium chloride solution, stirring for 0.5 h; the obtained polymer is vacuum filtered, dissolved in 10 mL of dimethyl sulfoxide DMSO, and then precipitated into 50 mL of acetone, stirring for 0.5 h; similarly, the precipitated polymer is filtered, and then dried in a vacuum at 40 to 150°C for 12 to 48 h to obtain an ionic polymer in the form of sodium ions; S4. Dissolve the ionic polymer in a polar solvent to obtain a solution with a concentration of 5wt% to 40wt%, centrifuge, cast it on a substrate or a porous substrate, and then vacuum dry it at 80°C for 12 hours to obtain a sodium ion exchange membrane with a thickness of 10 to 100μm; place the sodium ion exchange membrane in 1M sulfuric acid for 24 hours, then rinse it with deionized water to neutrality, and then place these membranes in deionized water for 24 hours, change the deionized water three times within 24 hours to obtain a proton exchange membrane.

2. The method for preparing a non-fluorinated proton exchange membrane with controllable sulfonation sites according to claim 1, characterized in that: The thickness of the porous substrate is 1 to 100 μm.

3. The method for preparing a non-fluorinated proton exchange membrane with controllable sulfonation sites according to claim 1, characterized in that: The polar solvent is one or more of NMP, DMF, DMSO and DMAc.

4. The method for preparing a non-fluorinated proton exchange membrane with controllable sulfonation sites according to claim 1, characterized in that: The substrate is one of stainless steel plate, glass plate, polyethylene terephthalate plastic PET plate, polypropylene PP plate, polyethylene naphthalate PEN plate; the porous substrate is one of polyphenylene sulfide PPS perforated plate, polyether ketone resin PEK perforated plate, polyethylene terephthalate plastic PET perforated plate, polytetrafluoroethylene perforated plate, stainless steel plate perforated plate, polypropylene PP perforated plate, polyethylene PE perforated plate, and glass fiber cloth.

5. A non-fluorinated proton exchange membrane with controllable sulfonation sites prepared by the method according to claims 1-4.

6. Use of the non-fluorinated proton exchange membrane with controllable sulfonation sites as claimed in claim 5 in the preparation of electrolyte materials for fuel cells and / or water electrolysis to produce hydrogen and / or flow batteries and / or electrodialysis.

Citation Information

Patent Citations

  • A densely sulfonated fluorinated polyarylether proton exchange membrane for vanadium redox flow batteries and its preparation method.

    CN110437438B

  • Fluoric proton exchange resins of polytrifluorostyrenes, synthesizing process and application thereof

    CN1128679C